Comparison of the Effectiveness of Parenting-Based Identity Formation Training and Positive Youth Development Training on Social Interaction Quality and Gender Schemas in Adolescent Girls - Tabandeh, Maryam; Mahdad, Ali; Sajjadian, Ilnaz (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to compare the effectiveness of parenting-based identity formation training and positive youth development training on social interaction quality and gender schemas in adolescent girls.Methods and Materials: The present research employed a quasi-experimental design with three stages: pretest, posttest, and follow-up, including a control group. The statistical population consisted of adolescent girls in Isfahan during the spring of 2024. From this population, 45 adolescent girls were selected through convenience sampling and assigned to three groups (15 participants per group). The Glass Social Interaction Quality Scale (1994) and the Bem Sex Role Inventory (1981) were administered to measure the dependent variables across the three stages. Both experimental groups participated in ten 60-minute training sessions, while the control group received no intervention. Data were analyzed using repeated measures analysis of variance and the Bonferroni post hoc test via SPSS version 26.Findings: The results showed a significant difference in social interaction quality between the parenting-based identity formation and positive youth development training groups compared to the control group, and in gender schema variables, a significant difference was observed only between the two intervention groups and the control group (p < .01). Furthermore, parenting-based identity formation training proved to be more effective than positive youth development training in improving social interaction quality and modifying gender schemas.Conclusion: Given the results, it is recommended that these two training approaches be incorporated into adolescent psychological counseling centers.